How does self-regulated learning influence formative assessment and summative grade? Comparing online and blended learners - Broadbent, Jaclyn; Sharman, Stefanie; Panadero, Ernesto; Fuller-Tyszkiewicz, Matthew (The Internet and higher education, 2021)
The literature regarding formative assessment and Self-Regulated Learning (SRL) has focused on the ways in which formative assessment improves SRL. This study, on the other hand, evaluated whether SRL characteristics impact successful engagement with formative assessment, and subsequent summative performance in both online and blended learning contexts. Ninety-six blended and 85 online learners completed a formative assessment task, received feedback, and then resubmit the assessment for a summative grade. Overall, while there were differences between learning contexts, SRL, and performance, many variables were not significant predictors of performance. Online learners who were confident, managed their time well and regulated their efforts saw the greatest benefits, though these effects were small when viewed individually. Blended learners, to a lesser extent, also benefited from confidence and effort regulation. To the authors' knowledge, this is the first study to test SRL characteristics as drivers of performance during a formative task across two learning contexts. •The first study to test SRL skills as drivers of performance during formative tasks.•SRL skills and grades were measured in two learning contexts: blended and online.•There were differences between learning contexts, SRL capabilities, and performance.•Successful online learners were confident, managed their time and efforts.•Successful blended learners were confident and regulated their effort.